Position Paper of the Ordre des infirmiéres et inﬁrmiers du Québec Perioperative Nursing Care : The Function of the Nurse as First Assistant - ORNAC, ORNAC (Operating Room Nurses Association of Canada Journal, 1995)
The Ordre des infirmieres et inﬁrmiers du Québec, in concert with various nurses associations and certain health care settings, is in favour of the recognition of the nurse’s function as first assistant. The nurse who assumes the function of first assistant during a surgical procedure is practising in the ﬁeld of perioperative care, and is acting within the framework of her professional practice. The majority of the first "assistant nurse’s activities are conducted in the presence of the surgeon, in interrelation with him, and under his direct supervision. The nurse thus provides the clinical and technical assistance necessary for the surgeon to operate safely, and in the best interests of the user.